2016
DOI: 10.3389/fpls.2016.00086
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Reference Genes for Normalization of MicroRNA Expression by RT-qPCR in Sugarcane Buds under Cold Stress

Abstract: Sugarcane, accounting for 80% of world's sugar, originates in the tropics but is cultivated mainly in the subtropics. Therefore, chilling injury frequently occurs and results in serious losses. Recent studies in various plant species have established microRNAs as key elements in the post-transcriptional regulation of response to biotic and abiotic stresses including cold stress. Though, its accuracy is largely influenced by the use of reference gene for normalization, quantitative PCR is undoubtedly a popular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 49 publications
0
37
0
Order By: Relevance
“…Primer amplification efficiency indicates the amplicon doubling rate of a specific primer pair during a PCR, which affects the accuracy of RT-qPCR data [4,40]. A good primer combination has an E value close to 100% [34,35]. In our study, the E values of the primers used to amplify the five candidate reference genes were between 94% and 98.5%.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Primer amplification efficiency indicates the amplicon doubling rate of a specific primer pair during a PCR, which affects the accuracy of RT-qPCR data [4,40]. A good primer combination has an E value close to 100% [34,35]. In our study, the E values of the primers used to amplify the five candidate reference genes were between 94% and 98.5%.…”
Section: Discussionmentioning
confidence: 70%
“…In these studies, it is vital to choose appropriate reference genes for obtaining accurate and reliable results. A good primer combination has an E value close to 100% [34,35]. However, there has been no systematic and accurate validation of these genes under various experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Illumina HiSeq2500 platform was used to sequence the library, thereby generating a total of 260,117,346 raw reads. The transcription levels of 20 conserved miRNAs (including published reliable references miR171 [32], miR166b [31], miR159a [49], miR396a [50] and miR166b [51] were obtained and analyzed. Eight putative reference RNA targets (miR472, miR428b, miR396a, miR166b, miR3954, miR160, miR162-3p and miR403) with a median expression and the smallest standard deviations were selected from high-throughput sequencing data for identifying the most suitable normalizer for miRNA qPCR in citrus infected by Xcc.…”
Section: Selection Of Candidate Reference Genes and Primer Designmentioning
confidence: 99%
“…Several studies have recently been performed for identifying appropriate reference genes for miRNA qPCR, of which the stem-loop method has been used more frequently. A set of miRNAs was selected for evaluation in plants, such as castor bean, cotton, watermelon, wheat and sugarcane [30][31][32][33]. Luo et al, 2014, found miR5059 and miR5072 were the best reference genes in different peach tissues under different abiotic stress treatments using poly(A)-tailed RT-qPCR approach [34].…”
Section: Introductionmentioning
confidence: 99%